STUDI IN SILICO MODIFIKASI POS TRANSLASI DISAIN VAKSIN CHIMERIC BERBASIS VIRUS LIKE PARTICLES HUMAN PAPILLOMAVIRUS DENGAN KAPSID VIRION L1 - Tambunan, Usman Sumo Friend; Parikesit, Arli Aditya; Tochary, Theo A.; Sugiono, Dedy (Makara Journal of Science, 2007)
Computational Study of Post Translation Modification in Chimeric Virus Like Particles Vaccine of Human Papilloma Virus with Virion Capsid L1. The Human Papillomavirus (HPV) infection has a tight correlation with the incidence of cervical cancer. Chimeric virus like particles (cVLP) has been developed as vaccine candidate for preventing cervical cancer. cVLPs are improvement of Virus Like Particles (VLP) by substituting the epitope of L1 HPV -18 and -52 protein to L1 HPV -16 protein. They are ANN1, ANN2, HMM1, and HMM2. The impact of post translation modification will be determined. Based on In Silico study, the dominant post translation modification is glycosylation